Notes to Philosophy 167: Class 7 -- Galileo's Two New Sciences: Projectile Motion -- Part 7. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Galileo's Determination of the Parabola -- The Significance of Galileo's Approach -- The Basic Claims Made by Galileo's Theory -- Mathematical Consequences of the Theory.; Generally corresponds to the video segment: Class 7, Part 7.